Population Dynamics of Goldstripe Sardinella (Sardinella gibbosa) in the Waters of Barru Regency, Province South Sulawesi - Untung, Melki; Amir, Faisal; Umar, Moh. Tauhid (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Goldstripe Sardinella (Sardinella gibbosa) is a type of small pelagic fish, of important economic value and is widely caught in the waters of Barru Regency which is the catch of lift net. This study aims to analyze the population dynamics of the Goldstripe Sardinella in the waters of Barru Regency, South Sulawesi. The data used in this study is primary data, namely direct data collection in the field in the form of measuring the length of the Goldstripe Sardinella sample. Sampling is carried out by measuring the catch of Goldstripe Sardinella using a stratified random sampling method . The number of Goldstripe Sardinella measured was 1,357 with a total length range of 100-190 mm. Found 3 age groups with average body length L1 = 116.4 mm , L2 = 145.4 mm, and L3 = 171 mm. Lâˆž = 211.0 mm, K = 0.50/year, and , t0 by -0.192 years. Z values = 1.69/year, M = 0.68/year with a water temperature of 29.8oC, and F = 1.01/year, as well as values E = 0.60 and Y/Râ€™ = 0.0585 g/recruit. This value shows that in the waters of Barru Regency can be categorized as waters that have been overexploited, although the value of rapid growth, fishing activities are also high, and if continuous fishing is carried out without fishing arrangements, the stock of Goldstripe Sardinella will be reduced and even will experience extinction.